Study on the effects of a medicated oil in the management of chronic wounds - Anpuchelvi, S.; Sritharan, G. (3rd INTERNATIONAL CONFERENCE ON AYURVEDA, UNANI, SIDDHA AND TRADITIONAL MEDICINE 2015, 2015)
Chronic wounds are frequently encountered problem in the present era produced due to the complications of trauma or pathological injury and it causes long-term agony to the patients. In the present study Pachai ennai was prepared and its wound healing properties were studied on various chronic wounds. Pachai ennai was prepared using the standardization procedure the effects were studied on 40 patients with chronic wounds (wounds more than 3 weeks old) selected from Herbal Health Care Centre, Kokuvil. The patients were divided into two groups - Group A (Pachai ennai dressing) and Group B (Normal Saline Gauze bandage). The drug was applied topically and patients were studied daily for 30 days and results were analyzed. In Chronic Wound the size was decreased 69.23% which was statistically highly significant. There was considerable improvement (> 80 %) in swelling and unhealthy margin. Pain, tenderness, discharge and unhealthy granulation tissue showed moderate effect (between 60 to 70 percent) in the chronic wounds. From the studies made from clinical cases, it was concluded that the drug "Pachai ennai " possess sufficient efficacy in Pun without producing any adverse effects.
Keywords: Pachai ennai; Herbal Health Care Centre; Pun